An Experience of Tourism Development: How is the Strategy? - RATNASARI, Sri Langgeng; SUSANTI, Ervin Nora; ISMANTO, Widodo; TANJUNG, Rona; DARMA, Dio Caisar; SUTJAHJO, Gandhi (Journal of Environmental Management and Tourism, 2020)
Tourism is a sector that can determine the economic welfare of local communities. Tourism development needs to pay attention to aspects of facilities, tourists, and local communities, so as to create sustainable integration. The objectivity of this study is to contribute to tourism development in Samarinda City with a strategy that involves organizational innovation, management knowledge, organizational learning, and leadership transformation in the tourism community (government, business actors, and society). To answer these objectives, we use a research-based R&D approach. With careful planning, we developed several strategies by involving the Agency of Culture, Tourism, Communication, and Information Technology of Samarinda City in order to create a culture of learning and knowledge sharing through various productive agendas. Focus on organizational management, need to apply knowledge ineffective and conducive work procedures as a serious process. Organizational learning is part of the creation of competitiveness by those involved in the tourism industry. This is related to organizational culture and systems that grow because it can bring new ideas to various parties. In addition, the objectives of tourism development must also pay attention to social, historical, cultural, economic, and environmental aspects.